2018
DOI: 10.1016/j.bbagen.2018.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Lysine as a heme iron ligand: A property common to three truncated hemoglobins from Chlamydomonas reinhardtii

Abstract: Primary structure analysis of hemoglobins has limited power in the prediction of heme ligation. Experimental determination reveals variations in this essential property across the superfamily.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 79 publications
(120 reference statements)
1
17
0
Order By: Relevance
“…LysE10 is conserved in Chlamydomonas THB10 and THB11, whose electronic absorption spectra indicate hexacoordination in the ferric state, but whose reduced (heme-Fe II ) forms are pentacoordinate according to UV-Vis spectroscopic and, in case of THB11, extended X-ray absorption fine structure (EXAFS) analyses [31]. The comparison of the structures of THB1 and THB4 and an analysis of primary sequence patterns suggested to determine hexacoordination in previous studies revealed no clear determinants of LysE10 hexacoordination so far [29]. Notably, a recent study of Chlamydomonas THB1 variants, in which LysE10 was exchanged by other residues, indicates that THB1 has an intrinsic structure favoring heme-Fe bis-coordination [36].…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…LysE10 is conserved in Chlamydomonas THB10 and THB11, whose electronic absorption spectra indicate hexacoordination in the ferric state, but whose reduced (heme-Fe II ) forms are pentacoordinate according to UV-Vis spectroscopic and, in case of THB11, extended X-ray absorption fine structure (EXAFS) analyses [31]. The comparison of the structures of THB1 and THB4 and an analysis of primary sequence patterns suggested to determine hexacoordination in previous studies revealed no clear determinants of LysE10 hexacoordination so far [29]. Notably, a recent study of Chlamydomonas THB1 variants, in which LysE10 was exchanged by other residues, indicates that THB1 has an intrinsic structure favoring heme-Fe bis-coordination [36].…”
Section: Introductionmentioning
confidence: 88%
“…The microalga contains at least 12 genes coding for class I 2/2Hbs (THB1-12) [16,27,28], and the encoded proteins are quite diverse. Whereas THB1, THB2 and THB4 represent single-domain Hbs [29,30], THB3 and THB5-THB12 feature extended N-and/or C-termini of so far unknown function (note that only THB1 to THB4 have assigned names in the Chlamydomonas genome annotation at Phytozome 12; the nomenclature of THB5 to THB12 follows that in Hemschemeier et al [27]). THB3 lacks the conserved proximal HisF8 residue, THB5 has four consecutive 2/2Hb domains and THB7 features a split globin domain [28,29,31].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations